Diaspora Philanthropy in the Context of Policy Coherence for Development: Implications for the post‐2015 Sustainable Development Agenda. (29th December 2016) - Koff, Harlan
Abstract: Thus far, there has been a dearth of studies that systemically examine the relationship between diaspora philanthropy, the development community and securitised migration regimes. This article addresses this by responding to the research question, "How coherent are securitised migration policies with diaspora philanthropy and the transformative development objectives that characterise the Sustainable Development Goals (SDGs) agenda?" The analysis is based on the concept of policy coherence for development (PCD). The article compares the simultaneous regionalization and securitization of European Union and United States migration policies and contends that these policy strategies undermine diaspora philanthropy, development partnerships and transformative development. Normative change must be introduced in order to establish coherence between globalized migration policies and diaspora philanthropy objectives. Normative coherence for development can be achieved by introducing principles from the SDG's and the Busan Development Partnership Agreement amongst other international development agendas, into migration policy‐making at the national and regional levels.